Kepemimpinan Pendidikan Islam Perspektif Agama - Suwelda, Suwelda; Ahmadi, Ahmadi; Ajhari, Ajhari; kiftiah, suwelda (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
This article discusses the concept of Islamic educational leadership from a multicultural perspective, focusing on its definition, essence, basic concepts according to the Qur’an, as well as the functions and roles of leadership in Islamic educational institutions. The study employs a literature review method by examining various relevant sources. The findings indicate that Islamic educational leadership is a leadership process based on the values of the Qur’an and Islamic teachings, emphasizing not only managerial aspects but also spiritual and moral dimensions. Leaders in Islamic education are expected to guide, motivate, and mobilize human resources within educational institutions to achieve Islamic educational goals aimed at forming well-mannered individuals who are responsible as caliphs on earth. Furthermore, Islamic educational leadership must create a conducive organizational climate, integrate Islamic values, and serve as role models for the entire academic community. Thus, effective Islamic educational leadership is crucial in building inclusive and multicultural educational institutions capable of addressing globalization challenges without losing Islamic identity.